2001
DOI: 10.1890/0012-9658(2001)082[2547:htsdar]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

How Tree Species Differ as Recruitment Foci in a Tropical Pasture

Abstract: In a Neotropical pasture, I predicted that two characteristics of trees, type of fruit produced and amount of shade cast, would affect recruitment and growth of woody plants underneath them. I also predicted that woody plants that persisted in active pasture would affect the species assemblages under trees after pasture abandonment. To investigate these hypotheses, I examined the assemblages of recruits under several types of trees in active pasture and also under similar trees that were fenced off (enclosed) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 24 publications
10
103
1
2
Order By: Relevance
“…Similar facilitative effects have been reported in successional processes (Slocum 2001, Yoshihara et al 2010 and in the process of riparian forest tree encroachment into savannah (Shararn et al 2009). Hennenberg et al (2006) reported that fires can occur frequently with high grass cover, but rarely with low grass cover.…”
Section: Establishment Of Montane Forest Trees In Miombo Woodlandsupporting
confidence: 78%
“…Similar facilitative effects have been reported in successional processes (Slocum 2001, Yoshihara et al 2010 and in the process of riparian forest tree encroachment into savannah (Shararn et al 2009). Hennenberg et al (2006) reported that fires can occur frequently with high grass cover, but rarely with low grass cover.…”
Section: Establishment Of Montane Forest Trees In Miombo Woodlandsupporting
confidence: 78%
“…In some cases, the average densities of plants were two (firewood, human food, livestock fodder, medicinal resources) or almost three (high-grade timber) times higher under Ficus trees than under non-Ficus trees. 2015, 44:678-684It appears likely that the higher densities of valuable plants growing under Ficus trees is a consequence of Ficus trees supporting higher plant densities per se, as has been demonstrated in studies from the Neotropics (Slocum 2001;Guevara et al 2004). However, the exact reasons for a higher density of useful plants growing under Ficus trees compared to non-Ficus trees are hard to disentangle.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, if the areas under isolated Ficus trees are well managed, they are likely to provide important resources for local households over long timescales, aligning conservation and development objectives through community resource management (Hutton and LeaderWilliams 2003;Adams et al 2004;Martin et al 2009). As the cost of reducing grazing and vegetation clearance under Ficus trees is low (Barnes et al 2014), and as Ficus trees occur in rural landscapes across the tropics (Slocum 2001;Guevara et al 2004;Eshiamwata et al 2006;Caughlin et al 2012), the conservation of Ficus trees and the plant communities associated with them could yield low-cost improvements to human welfare on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…Birds are widely used as bioindicators for the monitoring of ecosystems under restoration, as they commonly present fast responses to forest development [16][17][18] and perform important ecological functions such as pollination, seed dispersal, and predation [19][20][21]. Bird assemblages can show large shifts in their composition according to the vegetation successional stage [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%